Microwave Assisted Surface Treatment of Okra Fibers - (:unkn) unknown (IOP PUBLISHING LTD, 2018)
All over the world, the importance of the sustainable and biodegradable materials is increased very fast. The use of agricultural stem waste as a technical textile material can be made a huge contribution for save the environment. The aim of this research was to pre-treat the okra fibers with microwave energy. The fibers were obtained from Marmara Region agricultural waste by use a specially designed machine. They were microwave-assisted surface treated with 7 % sodium bisulphate and 10 % acetic acid. The results of tensile strength, fiber diameter, SEM and X-Ray analyses were compared to the conventionally treated fiber samples. Finally, microwave-assisted treatments were quite good. Bisulphate treatment was more effective than treatments with acetic acid. When the SEM images was investigated, a lot of porosity was observed on the surface of acetic acid treated fiber and the tensile strength values increased bisulphate treatment.
Keywords: agriculture waste; microwave energy; okra fibers; surface modification; NATURAL FIBER; COMPOSITES